Analysis of a new random multi-access MAC protocol and its energy efficiency for wireless sensor networks - DING Hong-wei; ZHAO Dong-feng; HUANG Mao-mao (Tongxin xuebao)
A novel random multi-access MAC protocol for WSN using the multi-channel and the probability detection and 1-persistent access policy in the packet transmit（1+a） was proposed.The throughputs of the PDPMRM protocol and the multi-traffic were obtained.Simulations agree with the theoretical analysis.Also,the energy efficiency was analyzed for WSN by choice of probability p to control the waking nodes in busy period and the sleeping nodes in idle period.The sleeping technique realized the purpose of saving energy.By using contrast of energy efficiency between PDPMRM and improved PDPMRM,this improved PDPMRM has longer life cycle,it is more suitable for WSN.